Permittivity and filtration properties of grout socks for rock bolt installations. Issue 3 (15th June 2022) - Lam, C.; Jefferis, S.A.
Abstract : Rock bolts are commonly used to stabilise slopes and underground excavations but their installation can sometimes be difficult in challenging grounds due to excessive leakage or washout of the grout. To manage these problems, tubular geotextile socks have been adopted in the industry but there has been a lack of research on their properties. To advance the understanding of sock behaviour, the water permittivity and filtration properties of two types of grout sock have been investigated in their unstretched state. From the permittivity tests, it is shown that water flow through these socks will be laminar and that using more than one layer in a setup can effectively reduce the flow velocity. Moreover, it has been shown that the effect of the tester should be considered in the analysis or else the permittivity of the geotextile could be underestimated. From the filtration tests, it is shown that both types of grout sock tested are effective in minimising grout loss and that the permittivity of the filter cake will be many orders of magnitude lower than that of the socks. The results also show that the water–cement ratio of the grout will be reduced as a result of the dewatering process.